PENGARUH REWARD FINANCIAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN DAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Ika Sari (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
Increasingly tight business competition has resulted in companies having to maintain the sustainability of their business. Financial Rewards is one of the ways to motivate to produce good financial performance. Financial performance shows the company's ability to generate income with resources owned by the company. The leadership style of a leader plays a major role in the formation of character and performance of company resources because employees will continue to adapt to the leadership style in the company until finally the employee can conquer it.The purpose of this study was to examine the effect of financial rewards and leadership styles on financial performance and motivation as intervening variables. This study tested the hypothesis by using the partial least square method. Sampling in this study using nonprobability (nonrandom selection) with convenience method resulting in 50 respondents. The results showed that the t-statistic value was 1.508 <1.96 (not significant), meaning financial compensation had no significant effect on motivation. The t-statistic value is 15,343> 1.96 (significant) this means that the leadership style has a significant effect on motivation. This t-statistic value of 2.209> 1.96 (significant) means that financial compensation has a significant effect on performance. The t-statistic value is 2.609> 1.96 (significant) this means that the leadership style has a significant effect on performance. The t-statistic value of 1.265 <1.96 (not significant) means that motivation has no significant effect on performance.